Sistem Koordinasi Simpang Bersinyal (Study Kasus Jalan MT. Haryono Kota Kendari) - Nuhun, Ridwan Syah; Sulha, Sulha; Sabri, Muhammad Sahara Mubarak (MEDIA KOMUNIKASI TEKNIK SIPIL, 2025)
Coordination of signalized intersections is an important aspect of urban traffic management which aims to increase the efficiency of vehicle movement and reduce congestion. Jalan MT. Haryono is one of the roads in Kendari City which often experiences traffic jams, especially during rush hours, where on this road section there are two signalized intersections close to each other, namely the Pasar Baru intersection and the GMT intersection, which are separated by a distance of 500 m. The aim of this research is to determine the optimal cycle time in implementing a coordinated signal system at an intersection. With the implementation of coordinated cycle times, the degree of saturation decreases and intersection performance increases because queue lengths and delays are successfully reduced. On weekdays, queue lengths drop to 122 m in the east and 76 m in the west, with delays reducing to 108 seconds in the east and 80 seconds in the west. Meanwhile, on holidays, queue length drops to 94 m in the east and 88 m in the west, with delays reduced to 85 seconds in the east and 76 seconds in the west.